Linseed: An oilseed crop harnessing the power of nature - Verma, Parkash; Supriya; Kumar, Rakesh; Kumar, Birendra; Krishna, Bal (Indian Farming, 2023)
Linseed, also known as flaxseed, is an oilseed crop that has gained significant attention in the field of agronomy due to its numerous benefits. With its versatile nature, linseed holds immense potential not only as a cash crop but also as a source of nutrition and industrial applications. The oil extracted from linseed is rich in omega-3 fatty acids, making it highly sought after in the food and health industry. Its nutritional properties contribute to improved cardiovascular health and cognitive function, leading to increased demand for linseed oil-based products such as cooking oils, dietary supplements, and salad dressings. Linseed also possesses high-quality fibre having remarkable properties, including high strength and absorbency, making it ideal for various applications. In the textile industry, linseed fibre is used to produce linen fabrics known for their durability, breathability, and luxurious feel. The plant also improves soil fertility, reduces soil erosion, and requires fewer pesticides and fertilizers compared to other crops. Moreover, the use of linseed plant as a whole to produce innovative industrial products would enhance the sustainability of natural resources.